Strategies for malaria elimination: An afro-colombian perspective (2019)
Objective To describe strategies for malaria elimination based on the perception of Afro-Colombian residents in Guapí, in the context of the Integrated Management Strategy for the Promotion, Prevention and Control of Vector-Borne Diseases in Colombia (EGI-ETV). Materials and Methods Qualitative study based on focus group discourse analysis. Eight participants from the urban area of Guapi were divided into two groups. The first group included three female nursing assistants, and was called “women with more experience”; they were workers in the current health system and former Malaria Eradication Service officers. The second group was made up of female nursing assistants, and was called “women with limited experience”; they were workers in the current health system and were not directly trained in the malaria program. An inductive and interpretative analysis was performed. Results Eight subcategories emerged, framed in the EGI-EVT, making emphasis on promotion and prevention aimed at reducing malaria, especially in rural areas. This problem must be addressed comprehensively, including other health issues and social determinants that affect them, such as: basic sanitation, access to health services, lack of education, use of popular treatments, and lack of infrastructure, among others. Conclusion Participants consider that malaria in Guapi can be reduced but not eliminated. This problem needs to be addressed from an institutional and community perspective, taking into account cultural differences, based on strategies that include community empowerment and administrative and institutional strengthening of the program. © 2019, Universidad Nacional de Colombia. All rights reserved.